Volume 5A: 39th Mechanisms and Robotics Conference 2015
DOI: 10.1115/detc2015-46516
|View full text |Cite
|
Sign up to set email alerts
|

A Meso-Scale Rolling-Contact Gripping Mechanism for Robotic Surgery

Abstract: A new, compact 2 degree-of-freedom mechanism 4.1 mm in diameter suitable for robotically controlled surgical operations is presented. Current commercially available robotically controlled instruments achieve high dexterity defined by three degrees of freedom and relatively confined swept volume at just under 1 cm in diameter. Current smaller diameter instruments result in high part count and large swept volumes (less dexterity). A meso-scale rolling contact gripping mechanism is proposed as an alternative. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The 3-mm L-Arm concept as designed has a total of six parts, four of which are unique. A lower part count compared to commercially available instruments could reduce cost and improve the availability of MIS procedures for a broad range of patients [16].…”
Section: Resultsmentioning
confidence: 99%
“…The 3-mm L-Arm concept as designed has a total of six parts, four of which are unique. A lower part count compared to commercially available instruments could reduce cost and improve the availability of MIS procedures for a broad range of patients [16].…”
Section: Resultsmentioning
confidence: 99%
“…The design of the joints is also vulnerable to torsion. We carried out preliminary tests on the mechanical properties of the gripper and found that the torsional stiffness can be increased by adding flaps laterally to the joint, as suggested by Grames et al 19 In the current design iteration, we decided to keep the design simple by not introducing additional elements, but in future work, it is advised to take torsion considerations into account in the gripper design.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional compliant rolling-contact element (CORE) joint involves joining two half cylinders with flexures. Derived from CORE, the Split CORE was integrated to a wrist design provided by Intuitive Surgical Inc. to create a 3 DoF gripping mechanism [105]. Lan et al [10] developed an adjustable constant-force forceps for robot-assisted surgical manipulation to aid in grasping soft tissues.…”
Section: Transmissionmentioning
confidence: 99%